Were Islamic Indices Resistant to Volatility During the COVID-19 Period? - Sumbul; Rizvi, Ziya Batul; Siddiqui, Saif (Indian Journal of Finance, 2024)
Purpose : We examined the volatility and dependency structure between the Islamic and conventional indices throughout the crisis in this study. Design/Methodology/Approach : The study used a dataset to analyze Islamic performance and its parent indices. By employing the GARCH model, we analyzed the volatility and dependency of the Copula model from January 1, 2017 to December 31, 2022. This period was subdivided into pre-COVID-19 and COVID-19 periods. Findings : The findings showed that the COVID-19 pandemic has harmed the financial sector, affected stock prices, and increased volatility in Indian stock markets. The GARCH results demonstrated that AR and MA had positive coefficients in all the markets. The market is resilient to stock market shocks, as indicated by the significance of coefficients Î± and Î². The dependency pattern in the post-COVID-19 cycle 2 was nearly identical as it was in the pre-COVID-19 for the majority of market sets. It showed that one market is dependent on another market. Research Limitations/Implications : The crisis did not influence the Islamic market. This study was limited to a few stock indices. The study could be expanded by adding global markets with more significant time durations. We used GARCH and Copula in this study; Wavelet and DCC-GARCH models will be used in further studies. Finally, it will be helpful for investors to make investment decisions related to portfolio diversification and create awareness among investors. Originality/Value : The study used econometric tools to examine dependency and volatility among the indices. It also analyzed whether Islamic indices performed better than their parent indices. A global framework with worldwide data was presented in this research. This could be accomplished using a worldwide analysis to avoid country-specific impacts.